Assay for galactose-deficient IgA1 enables mechanistic studies with primary cells from IgA nephropathy patients. (9th August 2018) - Reily, Colin; Rizk, Dana V; Julian, Bruce A; Novak, Jan
Aims: IgA nephropathy, the most common primary glomerulonephritis worldwide, is characterized by glomerular deposition of galactose-deficient IgA1 and elevated serum levels of this IgA1 glycoform. Current ELISA methods lack sensitivity to assess galactose deficiency using small amounts of IgA1, which limits studies in primary cells due to modest IgA1 production in isolated peripheral-blood lymphocytes.Methods: Lectin from Helix pomatia was conjugated to biotin or acridinium ester and used in ELISA to detect galactose deficiency of IgA1 using small amounts of IgA1.Results: Lectin conjugated to acridinium had an approximately a log-fold increased sensitivity compared with biotin-labeled lectin.Conclusions: The new method of using lectin from Helix pomatia conjugated to acridinium increased assay sensitivity, allowing future mechanistic studies with cultured primary cells.